Juline Beaujoun and Amjed Rasheed (2020). Syrian Crisis, Syrian Refugees: Voices from Jordan and Lebanon. London, Palgrave Macmillan, 163 pages (hardback), ISBN 978-3-030-35015-4 - Saidin, Mohd Irwan Syazli; Hossain, Zara (Journal of Al-Tamaddun, 2024)
This edited volume by Juline Beaujouan and Amjed Rasheed, former Durham University researchers, provides a comprehensive analysis of the impact of the Syrian refugee crisis on Lebanon and Jordan from social, cultural, and economic perspectives. Comprising 11 chapters, each authored by different experts, the book underscores the critical challenges and responses of these two countries to the refugee influx, revealing a complex political landscape aimed at delegitimizing the Syrian regime.